2015
DOI: 10.3389/fnins.2015.00272
|View full text |Cite
|
Sign up to set email alerts
|

Variations of high frequency parameter of heart rate variability following osteopathic manipulative treatment in healthy subjects compared to control group and sham therapy: randomized controlled trial

Abstract: Context: Heart Rate Variability (HRV) indicates how heart rate changes in response to inner and external stimuli. HRV is linked to health status and it is an indirect marker of the autonomic nervous system (ANS) function.Objective: To investigate the influence of osteopathic manipulative treatment (OMT) on cardiac autonomic modulation in healthy subjects, compared with sham therapy and control group.Methods: Sixty-six healthy subjects, both male and female, were included in the present 3-armed randomized place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
67
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 45 publications
5
67
1
2
Order By: Relevance
“…[39] Therefore, OMT could reduce the release of cytokines and the sympathetic activity creating a cascade of biological and neurological events able to modulate both inflammatory and ANS mechanisms. [40,41] …”
Section: Discussionmentioning
confidence: 99%
“…[39] Therefore, OMT could reduce the release of cytokines and the sympathetic activity creating a cascade of biological and neurological events able to modulate both inflammatory and ANS mechanisms. [40,41] …”
Section: Discussionmentioning
confidence: 99%
“…(7) Utilize OMT that decrease sympathoexcitation and promote increase parasympathetic activity. Studies of soft tissue techniques, balanced ligamentous tension, balanced membranous tension, and cranial sacral techniques have been associated with changes in parameters associated with increased parasympathetic activity and increased vagal control of heart rate [197,198]. In contrast, subjects receiving SMT techniques demonstrate changes (heart rate variability measures, skin conductance, increased heart rate and blood pressure) associated with decreased parasympathetic and increased sympathetic nervous system function [187,199e205].…”
Section: Specific Effects E Omt and Neurophysiological Processesmentioning
confidence: 99%
“…11 The cervical myofascial release technique dampened tilt-induced sympathetic prevalence significantly, as shown by a lower LF:HF ratio compared with that found after sham manipulation. 7 In a 2015 study, Ruffini et al 10 reported a significant increase in HF power as well as a reduction in LF:HF ratio in resting participants undergoing OMT, thus supporting the view that OMT influences autonomic neural modulation of HR by increasing parasympathetic activity and shifting sympathovagal balance toward vagal prevalence. 10 This experimental evidence suggests that OMT is a potentially powerful approach to enhance the parasympathetic input to the heart and hence prevent exaggerated stress-induced sympathetically driven cardiac activations.…”
mentioning
confidence: 92%
“…[4][5][6] In more recent years, by means of HRV measurement techniques, the impact of OMT (osteopathic manipulative treatment) on cardiac sympathovagal balance has been assessed. [7][8][9][10] For example, a single cervical OMT protocol (upper cervical spine manipulation) was applied to healthy normotensive participants under resting conditions, and its effects were compared with sham therapy ( placement of fingers with no pressure exerted). 9 The treatment resulted in an increase in the spectral power in the high-frequency (HF) band, indicative of parasympathetic modulation of heart rate (HR) and a decrease in the ratio of low-frequency (LF) to HF power (LF:HF), indicating sympathovagal balance, compared with the sham treatment.…”
mentioning
confidence: 99%